(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This article describes experimental work on organizing the educational process using cultural and historical values in the preparatory group of preschool educational organizations in preparing students for school education. During the study, the influence of national customs, traditions of hospitality , folk oral art and game technologies on the moral, mental and social development of children was analyzed. The results of the experiment show that the level of knowledge and mastery indicators of children have significantly increased.